A new lumbar fixation device alternative to pedicle-based stabilization for lumbar spine: In vitro cadaver investigation - Gömleksiz, Cengiz; Erbulut, Deniz Ufuk; Can, Halil; Kodigudla, Manoj Kumar; Kelkar, Amey V.; Kasapoglu, Eser; Özer, Ali Fahir; Goel, Vijay K. (Taylor and Francis Ltd., 2020)
Context: To evaluate the stability provided by a new bilateral fixation technique using an in vitro investigation for posterior lumbar segmental instrumentation. Design: Experimental cadaver study. In this study, we propose an alternative technique for a posterior lumbar fixation technique called “inferior-oblique transdiscal fixation” (IOTF). Setting: Study performed at Engineering Center for Orthopedic Research Exellence (ECORE) in Toledo University-Ohio. Participants: Six human lumbar cadaveric specimen used in this study. Interventions: In this study, we propose an alternative technique for a posterior lumbar fixation technique called “inferior-oblique transdiscal fixation” (IOTF). As a novel contribution to the classical technique, the entry point of the screw is the supero-lateral point of the intersecting line drawn between the corpus and the pedicle of the upper vertebra. This approach enables the fixation of two adjacent vertebrae using a single screw on each side without utilizing connecting rods. Outcome Measures: Flexion (Flex), extension (Ext), right and left lateral bending (LB & RB), and right and left axial rotation (LR & RR), and the position data were captured at each load step using the Optotrak motion measurement system and compared for IOTF and posterior transpedicular stabilization. Results: The Posterior stabilization system (PSS) and IOTF significantly reduced the ROM of L4-L5 segment compared to intact segment’s ROM. During axial rotation (AR) IOTF fused index segment more than PSS. Besides this, addition of transforaminal lumbar interbody fusion (TLIF) cage improved the stabilization of IOTF system during flexion, extension and lateral bending. Whereas, PSS yielded better fusion results during extension compared to IOTF with and without interbody fusion cages. Conclusions: We hypothesized that the new posterior bilateral system would significantly decrease motion compared to the intact spine. This cadaver study showed that the proposed new posterior fusion technique IOTF fused the index segment in a similar fashion to the classical pedicle screw fusion technique.
Keywords: Bilateral System; In Vitro Lumbar; Lumbar Fusion; Lumbar Spine; Pedicle Screw Fixation; Posterior Fixation